PEMANFAATAN GOOGLE FORM SEBAGAI PENDAFTARAN ONLINE SISWA BARU di MA SABILAL MUHTADIN TAHUN PELAJARAN 2021/2022 - Moh Gufroni; Dyan Yuliana; Zainul Munawwir (STKIP PGRI Situbondo, 2022)
New student registration is the initial gate that students and schools must go through in screening educational objects. An important event for a school, because this event is the starting point that determines the smooth running of a school's work. The purpose of this study was to determine the effectiveness and efficiency of using Google Form as an online student registration form at MA Sabilal Muhtadin. This type of research is descriptive qualitative. The subjects of this study were students of class X at MA Sabilal Muhtadin Pasir Putih Bungatan Situbondo which consisted of 10 students and 1 operator. Data collection techniques in this study are Observation, Interview, Documentation. The data analysis technique used in this study is data analysis using the Miles and Huberman analysis method. The results of data analysis show that the use of google forms is very helpful in an online registration process for new students at MA Sabilal Muhtadin so that the registration process runs effectively and efficiently.